PENINGKATAN PERAN PTK-PNF DALAM PEMBELAJARAN BERBASIS INFORMASI KOMPUTER DAN TEKNOLOGI - Rasid, Rasid (JIV-Jurnal Ilmiah Visi, 2008)
Under an assumption that in the present days information and communication technology plays an important role in teaching and learning process, this article discusses how ICT can support the attainment of learning achievement. Based on the empirical studies, it recommends the educators and the supporting staff of non-formal education to improve their skills in using ICT in non-formal education and apply them in the instructional activities.